The Influence of Service Convenience Affecting Intention to Use Future Park Rangsit Department Store: the Mediating Role of Perceived Behavioral Control of Thai Youths in Pathumthani Province - Paiboon, Thanaporn; Phungbanekruay, Jirapa (KKBS Journal of Business Administration and Accountancy, 2020)
The research aims 1) to study the level of service convenience affecting perceived behavioral control 2) to study the perceived behavioral control affecting intention to use Future Park Rangsit Department Store 3) to examine the extent to which perceived behavioral control mediated the relationship between the dimensions of service convenience and intention to use Future Park Rangsit Department Store. Data is collected from a sample group of 400 customers by using questionnaires as a tool to collect data. The data was analyzed statistically using frequency, average, standard deviation and multiple regression analysis by defining a confident value of 95%. The results of study revealed that service convenience positively impacted perceived behavioral control and perceived behavioral control positively impacted intention to use Future Park Rangsit Department Store. Moreover, the result of study revealed that perceived behavioral control only partially mediates the relationship between the service convenience dimensions and intention to use Future Park Rangsit Department Store